calculus

posted by .

F(x)= ln (cos theta)
f'(x)

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. calculus

    conic sections prove that the line x-2y+10=0 touches the ellipse 9x^2+64y^2=576 show that the equation of the normal to the ellipse x^2/a^2 + y^2/b^2 = 1 at the point (a cos theta, b sin theta ) is ax sin theta - by cos theta - (a^2-b^2) …
  2. Calculus

    I wanted to confirm that I solved these problems correctly (we had to convert the polar curves to Cartesian equations). 1.rcos(theta)=1 x=1 2.r=2*sin(theta)+2*cos(theta) r^2=2rsin(theta)+2rcos(theta) x^2+y^2=2y+2x (a little unsure …
  3. Physics

    An object is shot at 20m/s at an angle theta. The object lands 24m away. What is the angle?
  4. trigonometry

    can you correct the rest for me please? Express each as a function of theta: a. sin (270deg + theta)= cos theta b. cos (pi + theta)= -cos theta c. tan (810 + theta)= ?
  5. trigonometry

    can you correct the rest for me please? Express each as a function of theta: a. sin (270deg + theta)= cos theta b. cos (pi + theta)= -cos theta c. tan (810 + theta)= ?
  6. Algebra II

    Multiple Choice Which expression is NOT equivalent to 1?
  7. Trigonometry

    Prove the following identities: 1. (tan theta - sin theta)^2 + (1-cos theta)^2 = (1-sec theta) ^2 2. (1-2cos^2 theta) / sin theta cos theta = tan theta - cot theta 3. (sin theta + cos theta ) ^2 + (sin theta - cos theta ) ^2 = 2 Thank …
  8. Trigonometry

    Prove the following identities: 1. (tan theta - sin theta)^2 + (1-cos theta)^2 = (1-sec theta) ^2 2. (1-2cos^2 theta) / sin theta cos theta = tan theta - cot theta 3. (sin theta + cos theta ) ^2 + (sin theta - cos theta ) ^2 = 2 Thank …
  9. Calculus

    convert to polar: 2xy=3 A. r=sqrt(3sin theta cos theta) B. r=sqrt[(3sin theta cos theta)/2] C. r=[3/(2sin theta cos theta)] D.This cannot be converted without ambiguity.
  10. Calculus

    If cos of theta= -7/12 and theta is in quadrant 2 then find a. tan(theta) cot (theta)= b. csc(theta) tan(theta)= c. sin^2(theta)+ cos^2(theta)=

More Similar Questions